Genetic and phenotypic profiling of supranormal ejection fraction reveals decreased survival and underdiagnosed heart failure. (27th March 2022) - Forrest, Iain S.; Rocheleau, Ghislain; Bafna, Shantanu; Argulian, Edgar; Narula, Jagat; Natarajan, Pradeep; Do, Ron
Abstract : Aims: Individuals with supranormal left ventricular ejection fraction (snLVEF; LVEF >70%) have increased mortality. However, the genetic and phenotypic profile of snLVEF remains unknown. This study aimed to determine the relationship of both snLVEF genetic risk and phenotype with survival and underdiagnosed heart failure (HF). Methods and results: A snLVEF genetic risk score (GRS) was applied and cases of snLVEF were identified in 486 754 individuals across two population‐based cohorts (Bio Me Biobank and UK Biobank). The snLVEF GRS and phenotype were evaluated for association with survival, as well as HF diagnosis, markers, symptoms, and medications. Of 486 754 participants, the median age was 58 years, 20 069 (4.1%) died, and 10 088 (2.1%) had diagnosed HF. Both snLVEF GRS (hazard ratio [HR] 1.1 for top 10% vs. bottom 10% GRS; p  = 0.002) and phenotype (HR 1.4; p  = 0.003) were associated with increased all‐cause mortality. Both snLVEF GRS and phenotype were associated with reduced HF diagnosis (odds ratio [OR] 0.97 and OR 0.63, respectively; both p  ≤0.002). However, the snLVEF GRS and phenotype were both associated with elevated brain natriuretic peptide (BNP) levels (146 and 185 pg/ml increase, respectively; p  <0.001), including 268 out of 455 (59%) individuals with snLVEF phenotype who had BNP >100 pg/ml. Among 476 666 participants without HF diagnoses, snLVEF GRS and phenotype were associated with increased HF symptoms (e.g. exertional dyspnoea OR 1.4 and OR 1.3; p  <0.003) and HF medications (e.g. loop diuretic OR 1.2 and OR 1.03; p  <0.02). Associations were consistent in hypertensive individuals without cardiac comorbidities. Conclusions: Genetic predisposition to and presence of snLVEF are associated with decreased survival and underdiagnosed HF. Abstract : Graphical abstract of the study of supranormal left ventricular ejection fraction (snLVEF) in two biobanks. The study assessed the genetic and phenotypic characteristics of snLVEF. Sixteen genetic variants were found in a genome‐wide association study to be associated with snLVEF and were incorporated into a genetic risk score (GRS). Both snLVEF GRS and phenotype were associated with increased hazard ratio (HR) for mortality, including in heart failure (HF) and hypertension subgroups. Both snLVEF GRS and phenotype were associated with reduced odds ratio (OR) for HF diagnosis, but increased brain natriuretic peptide (BNP) levels and increased OR for HF symptoms and medications. Individuals with a genetic predisposition or phenotype of snLVEF have worse survival and may be underdiagnosed for HF. Further study is needed to define snLVEF in clinical guidelines for HF diagnosis and risk stratification.